Examining Cyberbullying Bystander Behavior Using a Multiple Goals Perspective - Jones, Sarah E (2014)
Cyberbullying, defined as any behavior performed through electronic or digital media by individuals or groups that repeatedly communicates hostile or aggressive messages intended to inflict harm or discomfort on others, is a widespread problem. Bystanders play an integral role in the initiation, maintenance, and prolonged presence of such aggressive behaviors, but have thus far been overlooked in cyberbullying literature. Cyberbullying bystanders are defined in this study as those who witness cyberbullying, either within or outside their personal social network(s) and whose available responses range from inaction to intervention. Operating from a social-ecological perspective and guided by multiple goals theories, this study used focus group methodology and found that cyberbullying bystanders have an impact on perpetration and victimization by way of multiple, distinct goals, which impact their choice of behavioral response. Bystanders’ goals and behaviors served to inform the creation of a cyberbullying bystander typology inclusive of five types: the oblivious/distant bystander, the entertained bystander, the conspiring bystander, the unintentional instigating bystander, and the active/empowered bystander. By allowing a thorough, nuanced understanding of bystanders’ role in cyberbullying, the study has significant implications for communication theory and practical application in the development of prevention and intervention efforts